Case series of 12 Bartonella quintana endocarditis from the Southwest Indian Ocean. - Ludivine Sarsiat; Thomas Garrigos; Linda Houhamdi; Olivier Dauwalder; Barbara Kuli; Eric Braunberger; Olivier Belmonte; Pierre-Edouard Fournier; Guillaume Miltgen (Public Library of Science (PLoS), 2023)
Background Bartonella spp. are fastidious bacteria frequently identified as the cause of blood culture-negative (BCN) endocarditis. However, Bartonella infections are difficult to diagnose in routine laboratory testing and their incidence is probably underestimated. We investigated the epidemiological and clinical features of Bartonella endocarditis cases diagnosed between 2009 and 2021 on Reunion Island (Southwest Indian Ocean). Method We retrospectively included all patients diagnosed with Bartonella endocarditis at Reunion Island University Hospital during this period. Endocarditis was diagnosed on the basis of microbiological findings, including serological tests (IFA) and PCR on cardiac valves, and the modified Duke criteria. We used then the multispacer typing (MST) method to genotype the available Bartonella strains. Findings We report 12 cases of B. quintana endocarditis on Reunion Island (83.3% in men, median patient age: 32 years). All the patients originated from the Comoros archipelago. The traditional risk factors for B. quintana infection (homelessness, alcoholism, exposure to body lice) were absent in all but two of the patients, who reported head louse infestations in childhood. Previous heart disease leading to valve dysfunction was recorded in 50% of patients. All patients underwent cardiac valve surgery and antimicrobial therapy with a regimen including doxycycline. All patients presented high C-reactive protein concentrations, anemia and negative blood cultures. The titer of IgG antibodies against Bartonella sp. exceeded 1:800 in 42% of patients. Specific PCR on cardiac valves confirmed the diagnosis of B. quintana endocarditis in all patients. Genotyping by the MST method was performed on four strains detected in preserved excised valves and was contributive for three, which displayed the MST6 genotype. Conclusions Bartonella quintana is an important cause of infective endocarditis in the Comoros archipelago and should be suspected in patients with mitral valve dysfunction and BCN from this area.